Numerical Investigation on Spray Characteristics With Upstream Flow Pulsation of a Pintle Injector - Xie, Yuan; Nie, Wansheng; Gao, Yuchao; Tong, Yiheng (Frontiers in Aerospace Engineering, 2022)
Volume of Fluid (VOF) model and adaptive mesh refinement (AMR) method are used to study the spray characteristics of a gas-liquid pintle injector and the effects of mass flow pulsation of liquid on it. By pintle injector, we mean this is a thrust adjusting device that changes the injection area through movable parts. The pressure pulsation in the supply pipeline is simulated by periodically changing the mass flow rate of the inlet. Spray characteristics with constant and pulsating upstream flows are compared with each other. Effect of frequency and amplitude of upstream liquid flow pulsation on the spray performance were studied. The results reveal that holding the mass flow rate of the upstream liquid flow constant, under the impact of gas flow, the liquid block, liquid filament and a large number of small droplets are peeled off from the liquid film. The film breakup position stays relatively fixed and the spray has a conical shape. However, when the upstream liquid flow is pulsating, the film breakup position changes periodically, and the spray has a "Christmas tree"-shape. The pulsation frequency has little effect on spray angle. But it strongly determines on the droplets size, and the spatial distribution of the spray. In addition, the pulsation amplitude can enhance the phenomenon of "Christmas-tree". With the increase of pulsation amplitude, the liquid film at the outlet of pintle injector appears a periodic phenomenon of "contraction-expansion".